2020
DOI: 10.1080/19490976.2020.1754714
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection induces glycan availability to promote ileum-specific changes in the microbiome aiding rotavirus virulence

Abstract: Multiple studies have identified changes within the gut microbiome in response to diarrheal-inducing bacterial pathogens. However, examination of the microbiome in response to viral pathogens remains understudied. Compounding this, many studies use fecal samples to assess microbiome composition; which may not accurately mirror changes within the small intestine, the primary site for most enteric virus infections. As a result, the functional significance of small intestinal microbiome shifts during infection is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 145 publications
(182 reference statements)
5
60
3
Order By: Relevance
“…An increase in alpha diversity relative to healthy controls was observed in the RV infected children. This observation contradicts previous studies, which recorded a decrease [ 14 , 15 , 18 ] or no effect on alpha diversity [ 19 ]. However, the increase in alpha diversity in the infected population could be due to the non-convergence of the family Enterobacteriaceae , which accounted for about 16 % and could not be further resolved at the level of genus/species.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An increase in alpha diversity relative to healthy controls was observed in the RV infected children. This observation contradicts previous studies, which recorded a decrease [ 14 , 15 , 18 ] or no effect on alpha diversity [ 19 ]. However, the increase in alpha diversity in the infected population could be due to the non-convergence of the family Enterobacteriaceae , which accounted for about 16 % and could not be further resolved at the level of genus/species.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors observed an increase in the abundance of Proteobacteria in RV infected children compared to the controls. More recently, Engevik et al [ 15 ] showed that RV infectivity and virulence are dependent on microbiome changes, particularly by elevated Proteobacteria and a decrease in abundance of Firmicutes. Gram-negative bacteria, especially Proteobacteria and Fusobacteria, can interfere with specific innate immune responses and cause severe gastritis expressing flagella or toxigenic lipopolysaccharides (LPS) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRV infection causes significant changes to the composition of the ileal microbiota by inducing mucin secretion from goblet cells ( Engevik et al., 2020 ). This compositional shift favors mucin-degrading bacteria Bacteroides and Akkermansia , which in turn could also promote mRV infection in vitro .…”
Section: Interactions Between Rotavirus Vaccines and The Gut Microbiomentioning
confidence: 99%
“…Infection by RV produces a shift in nutrient availability in the gut and induces goblet cells to release mucin, which promotes growth of mucin-degraders Bacteroides and Akkermansia members in mice ileum. Consumption of mucin by these bacteria may, in turn, decrease the protection exerted by mucin against RV infection [37]. It is not known at this stage whether high Ruminococcus levels would represent a protective factor against RV infection in children and, in fact, samples where Ruminococcus were detected derived from children suffering diarrhea.…”
Section: Discussionmentioning
confidence: 99%